2011
DOI: 10.1021/es200298t
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the Recalcitrant Pharmaceutical Compound Carbamazepine by Pleurotus ostreatus: Role of Cytochrome P450 Monooxygenase and Manganese Peroxidase

Abstract: Carbamazepine (CBZ) is an environmentally recalcitrant compound highly stable in soil and during wastewater treatment. In this study, we examined the mechanisms by which the white-rot fungus Pleurotus ostreatus metabolizes CBZ in liquid culture using a physiological approach. P. ostreatus PC9 was grown in media known to support different levels of a multiplicity of enzyme systems such as cytochrome P450 (CYP450) and manganese peroxidase (MnP). When both CYP450 and MnP systems were active, 99% of the added CBZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 29 publications
2
72
0
2
Order By: Relevance
“…Furthermore, intracellular enzymes, such as the cytochrome P450 enzyme system of fungus, are also reported to be helpful for TrOCs removal (Golan-Rozen et al, 2011), especially, in the context of this study, for diclofenac (Hata et al, 2010).…”
Section: Enzymatic Activity and Troc Removalmentioning
confidence: 83%
“…Furthermore, intracellular enzymes, such as the cytochrome P450 enzyme system of fungus, are also reported to be helpful for TrOCs removal (Golan-Rozen et al, 2011), especially, in the context of this study, for diclofenac (Hata et al, 2010).…”
Section: Enzymatic Activity and Troc Removalmentioning
confidence: 83%
“…These enzymes catalyze the degradation of recalcitrant pollutants over a wide range of pH [153,154]. In addition to the extracellular enzymes, Golan-Rozen et al [155] observed that the intracellular enzyme viz cytochrome P450 plays a vital role in CBZ degradation by whole-cell WRF. They demonstrated that the degradation of CBZ reduced from 99% to approximately 15% when cytochrome P450 was inhibited [155].…”
Section: White-rot Fungi and Their Extracellular Enzymesmentioning
confidence: 99%
“…In addition to the extracellular enzymes, Golan-Rozen et al [155] observed that the intracellular enzyme viz cytochrome P450 plays a vital role in CBZ degradation by whole-cell WRF. They demonstrated that the degradation of CBZ reduced from 99% to approximately 15% when cytochrome P450 was inhibited [155]. Whole-cell WRF and their extracellular enzymes have been studied extensively for enhanced removal of PhACs as depicted in Table 6.…”
Section: White-rot Fungi and Their Extracellular Enzymesmentioning
confidence: 99%
See 2 more Smart Citations